In two waters: contemporary evolution of lagoonal and marine white seabream (Diplodus sargus) populations - Gonzalez-Wangueemert, Mercedes (2016)
Brackish water ecosystems are often exposed to wide variations in environmental variables, including temperature and salinity, which may cause strong selective pressures on organisms modifying the genetic patterns of species. The aim of this work was to test whether there is a ‘divergence-with-gene flow’ in coastal lagoon populations of white seabream (Diplodus sargus) (Ria Formosa, S Portugal and Mar Menor, SE Spain) respect to four marine populations, by using partial sequences of cyt b mitochondrial gene and information from nine microsatellite loci. Genetic diversity was highest in both coastal lagoons (Mar Menor and Ria Formosa) considering mitochondrial and nuclear markers. Although some of FST population pairwise comparisons were not significant, analyses of molecular variance (AMOVAs) detected differences between groups (coastal lagoon and marine) close to significance. Also, only two haplotypes (Cytb-17 and Cytb-18) were detected in both coastal lagoon sampling sites and these localities (Mar Menor and Ria Formosa) showed the highest number of singletons, some of them with a high number of mutations, as has been already described for other Mar Menor populations (Pomatochistus marmoratus and Holothuria polii). Also, several tests detected significant positive and balancing selection considering mtDNA and microsatellite data. These data support the hypothesis of selection as one of the drivers of the genetic differences found between coastal lagoon and marine populations. The life strategy adopted by Diplodus sargus in coastal lagoons allows it to decrease its mortality rate and improve the heritability of its genes. Also, the increase time spent in coastal lagoons with different temperatures and salinities favours the fitness selection and the maintenance of exclusive haplotypes and genotypes in coastal lagoon inhabitants favouring the ‘divergence-with-gene-flow’.